Change and rigidity in youth employment patterns in Malawi - Benson, Todd; Erman, Alvina; Baulch, Bob (International Food Policy Research Institute, 2019)
Chapter 6 addresses Malawi’s weak agricultural transformation, and asks if rural households, particularly youth, are engaging in multiple forms of employment that may not be adequately reflected in national data.